Experts’ Perspectives on a Frontier in Cancer Prevention: A Qualitative Study - Potaya , Soparn; Thongcharoen, Vilaiwan (Royal Thai Air Force Medical Gazette, 2025)
Cancer is a leading cause of death in Thailand. Approximately 40 % of cancer can be prevented by changing behaviors or avoiding cancer risk factors. This qualitative research aims to explore experts’ perspectives on a frontier in preventable cancers prevention. Individual, in-depth interviews with thirty experts on cancer were selected using stratified purposeful sampling. A qualitative content analysis of the data revealed that the frontier in cancer prevention was determined by seven factors, including 1) setting clear policies and goals; 2) local area data utilization; 3) reaching the target audience; 4) promoting health literacy; 5) working with the local community; 6) vaccination; and 7) monitoring, evaluating the results, and improving the plan. These findings can be used to determine strategy for cancer prevention according to needs and suitable for the context of Thailand.